2020
DOI: 10.1038/s41375-020-0813-1
|View full text |Cite
|
Sign up to set email alerts
|

Pomalidomide, dexamethasone, and daratumumab in relapsed refractory multiple myeloma after lenalidomide treatment

Abstract: Patients with multiple myeloma who have relapsed after or become refractory to lenalidomide in early treatment lines represent a clinically important population in need of effective therapies. The safety and efficacy of pomalidomide, low-dose dexamethasone, and daratumumab was evaluated in lenalidomide-pretreated patients with relapsed or refractory multiple myeloma (RRMM) after one to two prior treatment lines in the phase 2 MM-014 study. Patients received pomalidomide 4 mg daily from days 1–21 and dexamethas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 41 publications
2
69
0
2
Order By: Relevance
“…Daratumumab has also been combined with pomalidomide, based on phase Ib data 61 and a nonrandomized, multicohort multicenter phase II study. 62 With this drug's promising results in relapsed and refractory multiple myeloma, trials evaluating daratumumab in transplant ineligible patients with newly diagnosed multiple myeloma showed significantly improved overall response rates and progression free survival. In the MAIA trial, daratumumab was combined with lenalidomide and dexamethasone (not reached v 31.9 months).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Daratumumab has also been combined with pomalidomide, based on phase Ib data 61 and a nonrandomized, multicohort multicenter phase II study. 62 With this drug's promising results in relapsed and refractory multiple myeloma, trials evaluating daratumumab in transplant ineligible patients with newly diagnosed multiple myeloma showed significantly improved overall response rates and progression free survival. In the MAIA trial, daratumumab was combined with lenalidomide and dexamethasone (not reached v 31.9 months).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…In randomized phase III studies of relapsed and refractory multiple myeloma, daratumumab and dexamethasone were combined with bortezomib (median progression free survival 16.7 v 7.1 months),4344 lenalidomide (44.5 v 17.5 months),454647 carfilzomib (not reached v 15.8 months),48 showing significant improvements in overall response rates and progression free survival. Daratumumab has also been combined with pomalidomide, based on phase Ib data61 and a non-randomized, multicohort multicenter phase II study 62. With this drug’s promising results in relapsed and refractory multiple myeloma, trials evaluating daratumumab in transplant ineligible patients with newly diagnosed multiple myeloma showed significantly improved overall response rates and progression free survival.…”
Section: Current Immunotherapiesmentioning
confidence: 99%
“…While randomized phase 3 data is awaited from the APOLLO study (NCT03180736) evaluating the benefit of adding daratumumab to pomalidomide and dexamethasone (Pd) in early RRMM, two phase 2 studies have demonstrated the strong efficacy of this combination. 5 , 6 In particular, the phase 2 MM-014 study enrolled patients with early RRMM with 1-2 lines of prior therapy. Among 84 lenalidomide-refractory patients, median PFS was 21.8 months, suggesting that durable responses can be attained even without a class switch away from IMiD-based therapy in patients progressing on lenalidomide.…”
Section: Casementioning
confidence: 99%
“…Treatment schema. References for suggested regimens: V‐Pom‐d,28,29 K‐Pom‐d, 30 D‐Pom‐d, 31 D‐V‐d, 32,33 K‐R‐d, 34 K‐Cy‐d, 35‐37 D‐R‐d, 38,39 Elo‐R‐d, 40 Ixa‐R‐d, 41 Pom‐Cy‐d, 42,43 D‐K‐d, 44 Sel‐V‐d 45 . *Regimens with phase 1/2 data…”
Section: Overview Of Myeloma Relapse Post First Asctmentioning
confidence: 99%
“…Median PFS for lenalidomide refractory patinets was 21.8 months. Out of 112 patients, 12 patients achieved ≥ CR including 3 patients with MRD negativity (10 −5 ) by NGS 31 …”
Section: Available Regimens From Randomized Clinical Trialsmentioning
confidence: 99%